G313 Introducing practical quality improvement techniques from first principles: an experience from myanmar. (24th May 2017) - Malley, M; Monaghan, M; Oo, SS; Roche, E; Babu, P; Bowyer, J; Halbert, J
Abstract : Aims: Healthcare in Myanmar is evolving. This includes the use of evidence based quality improvement, a novel concept for many senior clinicians. Royal College of Paediatrics and Child Health (RCPCH) Global Links Volunteers (GLVs) aimed to deliver audit-based quality improvement teaching to 26 senior local paediatricians (consultants and senior registrars) at 3 sites in central Myanmar. We aimed to assess pre-existing knowledge and post-session motivation to affect change. Methods: We devised a half-day simulated quality improvement project (QIP), including an interactive lecture along with simulated data collection and analysis. Each participant thus completed a full QIP cycle. Clinicians then discussed QIP ideas to apply to their own hospitals. One month later they completed a questionnaire to assess the impact of the session. Results: Of fifteen respondents, 80% had never experienced quality improvement teaching and over half were unaware of QIP activity ever having occurred in their hospitals. Post-session, 66% of respondents reported they had discussed starting a QIP in their hospital, all whom cited specific examples. 87% reported an intention to start a QIP in the near future and 100% reported feeling more confident regarding the process. The participants seemed motivated, with 100% reporting they felt performing QIPs would make tangible improvements to their hospital, and 100% citing the purpose of a QIP as 'improvement of patient care'. Despite this none of the respondents had actually started a QIP. Post-session, 33% of respondents reported delivering QIP teaching to local colleagues and thereby encouraging wider participation in quality improvement. They appeared to have retained the information delivered, with 100% correctly explaining the steps of the QIP cycle. Conclusions: Interactive practical QIP teaching represents a simple and reproducible model to educate and enthuse senior clinicians with limited previous QIP experience. This enthusiasm appeared to remain 4–6 weeks post teaching. Newly-acquired knowledge had also been disseminated to others. While many respondents reported interest in specific QIPs of their own, none had been realised. This signals both the need and opportunity for on-going partnership to put theory into practice, and continue the evolution of a supportive culture of quality improvement across Myanmar, while further work might assess the barriers to achieving this.